Innovative aspects of the teaching-learning-assessment of mathematics in high school in the context of developing XXI century skills - LUPU, Ilie; DRUTA, Rodica (Acta et Commentationes, Sciences of Education, 2023)
The „informational explosion” phenomenon, but also the reconceptualization of the mathematics curriculum, involves the exploration of new ways of teaching-learning-evaluation in the mathematical discipline, in order to train and develop the skills of the 21st century. Therefore, the formation of these skills amplifies the effort of the teacher and the student, imposing the expansion of the space and time limits of the traditional lesson. This article suggests answers to innovative, strategic and applied issues for mathematics teachers.